Prevalence and genetic diversity of Blastocystis sp. among autochthonous and immigrant patients in Italy - Marianna, Marangi (2023)
The prevalence of Blastocystis sp., its genetic diversity and the distribution of circulating subtypes (STs) were molecularly investigated in a cohort of autochthonous and immigrant patients with gastrointestinal symptoms hospitalized over the period February 2022–June 2023 at the Policlinico Ospedaliero-Universitario “Riuniti”, Foggia, in Southern Italy. The population variables, including patient geographical origin, gender and age classes were reported. Out of the 927 investigated patients, 36 (3.9%) were positive for Blastocystis sp. A statistically significant association with African origin and age classes >18 years old was found. ST1 (allele 4), ST2 (alleles 9, 13), ST3 (alleles 34, 36) and ST4 (allele 92) were the subtypes detected with a different distribution between autochthonous and immigrant patients. Co-infections with enteric protozoa such as Giardia duodenalis and Dientamoeba fragilis, pathogenic bacteria as Clostridioides difficile, Campylobacter jejuni and Aeromonas sp. and viral infections such as Norovirus were found in 33% of cases. This is the first study of Blastocystis sp., its circulating subtypes and allele variability among patients with different geographical origin in an area of Southern Italy, in the Central Mediterranean, characterized by high immigrant pressure. These results provide baseline data to better investigate a potential interaction between Blastocystis sp. and other risk factors in patients with gastrointestinal symptoms.